Defect dipole induced large recoverable strain and high energy-storage density in lead-free Na0.5Bi0.5TiO3-based systems - Cao, Wenping; Li, Weili; Feng, Yu; Bai, Terigele; Qiao, Yulong; Hou, Yafei; Zhang, Tiandong; Yu, Yang; Fei, Weidong (Applied physics letters, 2016)
In this letter, we propose an effective route to obtain large recoverable strain, purely electrostrictive effects and high energy-storage density by inducing defect dipoles into Na0.5Bi0.5TiO3 (NBT)-based relaxor ferroelectrics. It has been found that pinched and double polarization hysteresis loops with high maximum polarization (P max) and negligible remanent polarization (P r) can be observed due to the presence of acceptor-induced defect dipoles. A large recoverable strain of 0.24% with very little hysteresis and high electrostriction coefficient of 0.022 m4 C2 with purely electrostrictive characteristics were acquired when 11 mol. ‰ Mn-doped. Meanwhile, a high recoverable energy density of 1.06 J/cm3 with excellent temperature stability was obtained at the same composition owing to the enlarged value of P max-P r (36.8 μC/cm2) and relatively high electric field (95 kV/cm). Our achievement can open up the exciting opportunities for ferroelectric materials in high-precision positioning devices and high electric power pulse energy storage applications.